The Existence and Implementation of Customary Law in Acehnese Society Viewed from a Juridical Perspective - Sitompul, Theodore Daniel; Rahmadia, Mohamad Haikal; Suparba, Raden Dzaky Muhtadi Abhista; Fasya Akbar, Muhammad Rayhan; Fadhilah, Muhamad Arif; Aulia, Fara; Mulyadi, Mulyadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research examines the existence and implementation of customary law in Acehnese society through a normative juridical approach. Aceh is a province whose capital is Banda Aceh, and is located at the northern tip of the island of Sumatra. Aceh has a long history as a center for the spread, culture and religion of Islam in Indonesia, so it is called the